2020
DOI: 10.1371/journal.pone.0243951
|View full text |Cite
|
Sign up to set email alerts
|

A tuberculin skin test survey among healthcare workers in two public tertiary care hospitals in Bangladesh

Abstract: In Bangladesh, there is currently no data on the burden of latent TB infection (LTBI) amongst hospital healthcare workers (HCWs). This study aimed to determine the prevalence of LTBI and compare the prevalence among HCWs in two public tertiary care hospitals. Between September 2018 and August 2019, we conducted a cross-sectional study in two public tertiary care general hospitals. Using a survey and tuberculin skin test (TST), we assessed risk factors for LTBI, adjusting for known and plausible confounders. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Second, this study was conducted in 11 hospitals that were not randomly selected and therefore, the findings may not be generalizable to all hospitals that provide care to TB patients. However, this study findings are consistent with prior reports and studies conducted in other government and non-government hospitals in Bangladesh [ 7 , 10 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Second, this study was conducted in 11 hospitals that were not randomly selected and therefore, the findings may not be generalizable to all hospitals that provide care to TB patients. However, this study findings are consistent with prior reports and studies conducted in other government and non-government hospitals in Bangladesh [ 7 , 10 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…In middle- and low-income high TB-burden countries, all healthcare workers (HCWs) are at risk of TB exposure due to the presence of presumptive and or confirmed TB patients in the hospital [ 5 7 ]. Public tertiary care hospitals often lack basic infection prevention and control (IPC) measures that make HCWs more vulnerable [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the reported TB disease among HCWs may be attributable to the exposure to untreated TB patients in the hospital wards. This theory is supported by the findings from a companion study conducted in the same hospitals, which found that 42% of the HCWs were positive with a tuberculin skin test and HCWs at the medicine wards were 3.65 (95% CCI: 2.01-6.79) times more likely to be positive with TST when compared with administrative workers in the hospital [28].…”
Section: Discussionmentioning
confidence: 71%
“…There was the minimal implementation of TB IPC measures in public tertiary care general hospitals [ 3 ]. In addition, pulmonary TB patients in inpatients wards with limited or no IPC measures have been shown to increase HCW exposure to TB, resulting in 42% of latent TB infections among HCW [ 4 ].…”
Section: Introductionmentioning
confidence: 99%